Ulama's Role in Addressing Public Health Needs: The Case for or Against Breast Milk Banks? - Misbachussurur; Khashogi, ‪Luqman Rico (Jurnal Syariah dan Hukum Komparatif, 2024)
This research aims to analyze the legal and ethical implications of establishing breast milk banks (Bank ASI) in Indonesia, focusing on the differing opinions of contemporary Islamic scholars (ulama) regarding their permissibility. With the potential for a shift from donation-based systems to a commercial model, it is crucial to understand the moral and legal ramifications that may arise within the Muslim community. This study seeks to provide insights into how these banks can operate without conflicting with Islamic principles, thereby contributing to public discourse on this pressing issue. The research employs a qualitative approach, utilizing a literature review and comparative analysis of the views held by two prominent ulama: Hasbi ash-Shiddieqy, who supports the establishment of breast milk banks, and Umar Hubeis, who opposes them. Both scholars share a common educational background under Sheikh Ahmad Surkati, yet they arrive at divergent conclusions regarding the operational framework of breast milk banks. The study examines their arguments in detail, particularly focusing on the implications of milk mixing and its effects on familial relationships (radha'ah) as outlined in Islamic jurisprudence. In conclusion, this research highlights the complexities surrounding the establishment of breast milk banks in Indonesia from an Islamic legal perspective. The contrasting views of ash-Shiddieqy and Hubeis illustrate the ongoing debate within the scholarly community about how modern practices intersect with traditional Islamic values. By fostering dialogue among scholars and practitioners, this study contributes to a deeper understanding of how breast milk banks can be integrated into Muslim societies while respecting ethical and religious considerations.